The Influence Of Environmental Performance And Good Corporate Governance On Company Value - Ni Luh Putu Ratna Wahyu LESTARI; Anak Agung Ngurah Mayun NARINDRA (Indonesia Strategic Sustainability, 2022)
The value of the company is an indicator of the company in terms of fulfilling its obligations to investors, the value of the company also reflects the sustainability of the company in the future. However, there are many cases of environmental pollution in Indonesia, such as the case of PT. Lapindo Brantas Inc. who made negligence in drilling oil and gas in Sidoarjo had a negative impact on society, the environment and resulted in the decline in the share price of PT. Energi Mega Persada, Tbk. (major shareholder of PT. Lapindo Brantas Inc). In addition, there is also a case of PT. Freeport is currently the concern of various parties related to the change in the status of the contract of work owned by PT. Freeport became a Special Mining Business License (IUPK). This study aims to determine the effect of environmental performance and good corporate governance on firm value on IDX LQ45 index companies for the 2017-2021 period. The sampling technique used is purposive sampling technique so as to obtain 45 sample companies. The data analysis technique used in this study is multiple linear regression. This test shows that environmental performance and good corporate governance have a positive and significant effect on firm value on the Indonesia Stock Exchange.